Development of Articulate Storyline-Based Interactive Multimedia for Teaching Human Digestive System in Elementary School - Yuliana Rahmawati; Adi Bandono; Agung Pramujiono (Poltanesa, 2025)
This research addresses the need for interactive learning media in elementary education, specifically for teaching the human digestive system. The study aims to develop, validate, and assess the effectiveness of interactive multimedia based on Articulate Storyline for Grade V elementary school students. Using the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation), this research was conducted at SDN Sambirejo 1 with 28 fifth-grade students. Data collection involved validation questionnaires for media and material experts, practitioner questionnaires, pretest, and posttest assessments. The validation results showed very high feasibility ratings from media experts (92%), material experts (95%), and peer reviewers (95%), with an overall validation score of 94.81%. The multimedia's effectiveness was demonstrated through significant improvement in student learning outcomes, with the percentage of students achieving mastery (≥70) increasing from 32.14% in the pretest to 89.29% in the posttest, representing a 57.15% improvement. The average student score increased by 30.54 points, from 57.86 to 88.39. These findings indicate that Articulate Storyline-based interactive multimedia is highly feasible and significantly effective in enhancing student understanding of the human digestive system, demonstrating the potential of interactive technology in elementary science education